A simplified model for the effect of interfinger metal on maximum temperature rise in a multifinger bipolar transistor. - Walkey, D.J.
The prediction of a simple lumped representation of heat sharing through emitter interconnect in high-power multiemitter bipolar devices is compared to numerical thermal simulation and found to exhibit nonphysical results. Using numerical simulation, interfinger metal heat flow is characterized qualitatively in three dimensions and the requirements for a more accurate model are determined. A new modeling approach based on these insights, using segmented emitters and a coarse representation of the metal structure, yields results within 2% of those obtained from numerical thermal simulation for a wide variety of device geometries and substrate materials, with a simulation time reduction of more than an order of magnitude. Using the new model, an extensive series of simulations is performed for devices fabricated in Si, GaAs, and InP substrates using Al and Au for metallization. Reduction in maximum temperature due to the presence of emitter interconnect in these structures is found to be in the range of 5%-15%.
Keywords: Al; Al metallization; Au; Au metallization; GaAs; GaAs substrate; InP; InP substrate; Si; Si substrate; Emitter interconnect; Heat flow; High-power multiemitter bipolar device; Interfinger metal effect; Lumped model; Maximum temperature rise; Multifinger bipolar transistor; Numerical simulation; Three-dimensional thermal model